PURA LINGSAR DALAM PENDEKATAN TEOLOGI HINDU - Sumertha, I Wayan (Widya Sandhi, 2018)
Lingsar Temple, is a place of worship for two ethnicities and two religions namely Hindu Balinese ethnic, and Islam Wetu Telu ethnic Sasak. This phenomenon is something unique and unique in Lombok. Its uniqueness and uniqueness invite various audiences including academics to carry out various studies related to the values stored in it. Lingsar Temple as a symbol of monumental harmony of religious life in Lombok in particular and Indonesia in general. Likewise among tourists, both foreign and domestic, it is the main attraction as a leading tourist attraction for West Lombok regency in Lombok. Various values are contained in it, but the author is interested in researching the theological values that underlie Lingsar Temple. Based on a number of findings, it can be explained that the theology that underlies Lingsar Temple further emphasizes the worship of "Istadewata", namely: The worship of Lord Shiva as a god in Mount (Agung and Rinjani), as a symbol of Mahadewa Shiva on Mount Kailasa. Lord Lingsar in the form of Spring as a symbol of Lord Vishnu as the Preserver God, manifested in the form of a statue of Garuda Wisnu, and the Goddess Gangga which is realized in the form of a statue or statue of a goddess (beautiful girl). The dynamism found in Kemaliq Lingsar in the form of stones or called "pedewaq" or "pralingga." Which functioned as a medium of worship both by the Wetu Telu Islamic Community of the Sasak ethnic group, as well as the ethnic Balinese Hindu Community in Lombok.